Cardiovascular Effects of Whole-Body Cryotherapy in Non-professional Athletes - Coppi, Francesca; Pinti, Marcello; Selleri, Valentina; Zanini, Giada; D'Alisera, Roberta; Latessa, Pasqualino Maietta; Tripi, Ferdinando; Savino, Gustavo; Cossarizza, Andrea; Nasi, Milena; Mattioli, Anna Vittoria (Frontiers in Cardiovascular Medicine, 2022)
Objectives: The study aimed to investigate changes in heart rate, blood pressure, respiratory rate, oxygen saturation, and body temperature in non-professional trained runners during whole body cryotherapy (WBC). Methods: Ten middle-distance runners received 3 once-a-day sessions of WBC. Subjects underwent BP measurements and ECG recorded before and immediately after the daily WBC session. During WBC we recorded a single lead trace (D1) for heart rhythm control. In addition, the 5 vital signs Blood pressure, heart rate, respiratory rate, oxygen saturation and body temperature were monitored before, during and after all WBC session. Results: We did not report significant changes in ECG main intervals (PR, QT, and QTc). The mean heart rate before WBC was 51.75 + 4.56, changed to 57.23 + 5.12 during WBC and to 61.5 + 3.67 after session (p<0.05). The mean systolic blood pressure did not change significantly during and after WBC (baseline: 118 + 6, changed to 119 + 4 during WBC and to 118 + 3 after session (p<0.05).Mean respiratory rate did not change during WBC as well as oxygen saturations (98% versus 99%). Body temperature was slightly increased after WBC, however it remains within physiological values Conclusion: In non-professional athletes WBC did not affect cardiovascular response and can be safely used. However, further studies are required to confirm these promising results of safety in elderly non-athlete subjects.